Comparative study of sawdust media and fermented mixture of sawdust-cow dung for rearing Oryctes rhinoceros (Coleoptera: Scarabaeidae) larvae - Sat Rahayuwati; Yayi Munara Kusuma (Penerbit Universiti Kebangsaan Malaysia, 2024)
Newly emerged Oryctes rhinoceros (Coleoptera: Scarabaeidae) adults are required to test the virulence isolates of Alphanudivirus oryrhinocerotis (Lefavirales: Nudiviridae). Alphanudivirus oryrhinocerotis was formerly known as Oryctes rhinoceros nudivirus (OrNV). The tested emerging adults were all in healthy condition and uniform in age. This study aimed to analyze two types of breeding media for O. rhinoceros larvae: sawdust media (SM) and a mixture of sawdust and cow dung in a 1:1 ratio (MSC), the latter media had been fermented for three months. For the experiment, second- and third-instar O. rhinoceros larvae were maintained in 2-liter containers containing moist SM until they metamorphosed into adults. Male and female adults emerging from the SM were then placed together in a container with some sawdust, fed with sugar cane, and their lifespans were observed. The MSC medium was used to maintain third-instar O. rhinoceros larvae until they developed into adults. The emerged adults from the MSC were individually placed in 2-liter containers with some sawdust and sugar cane as food, and their lifespans were observed. Various parameters were measured, including the number of days it took for larvae to develop from third instar into adults, the percentage of adult emergence, sex ratio, infection rate of Metarhizium anisopliae fungi, the mean lifespan of adults in the laboratory, and the longest individual survival time. The research showed that SM and MSC media did not make a significant difference in the percentage of adult emergence, sex ratio, and M. anisopliae infection rate. Group maintenance of O. rhinoceros imagoes results in longer age compared to single maintenance. Females kept in groups have a longer lifespan than males, and males kept singly have a longer lifespan than females. Adults with a length of 4 cm were produced from third-instar larvae reared in both SM and MSC media. Based on this finding, the sawdust media is suggested to be used as breeding media for O. rhinoceros larvae for economical and practical reasons.